Keefektifan Metode Pembelajaran Peer Tutoring terhadap Keterampilan Menulis Teks Cerpen Siswa Kelas XI IPA 3 SMA Negeri 2 Gowa - Ananda Reski Novalia; Muhammad Saleh; Azis Azis (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract: This study aims to (1) determine the differences in the short story writing skills of students in class XI IPA 3 SMA Negeri 2 Gowa before and after using the peer tutoring learning method (2) prove the effectiveness of the use of peer tutoring learning methods on the short story writing skills of students in class XI IPA 3 SMA Negeri 2 Gowa. The type of research used in this research is experimental research